2015
DOI: 10.14310/horm.2002.1592
|View full text |Cite
|
Sign up to set email alerts
|

Lipid accumulation product is associated with metabolic syndrome in women with polycystic ovary syndrome

Abstract: oBJectIVe: there is a need for a simple and accurate method for the assessment of cardiovascular risk in polycystic ovary syndrome (Pcos). Lipid accumulation product (LAP) is based on the assessment of waist circumference and serum triglycerides that yield an estimation of lipid overaccumulation. we aimed to determine whether LAP is associated with metabolic syndrome (Mets) in caucasian women with Pcos. desIGn: we studied 222 women with Pcos who were diagnosed using the Rotterdam criteria. In all the subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
4
13
1
Order By: Relevance
“…marker of IR, MetS, cardiovascular risk and mortality in non-PCOS populations (13,28,51) as well as in PCOS population (15,16,52). Previously we showed that LAP was the strongest predictor of MetS defined by three different international criteria in Caucasian women with PCOS (19). In the present study, we have confirmed that LAP is an independent predictor of MetS in each PCOS phenotype.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…marker of IR, MetS, cardiovascular risk and mortality in non-PCOS populations (13,28,51) as well as in PCOS population (15,16,52). Previously we showed that LAP was the strongest predictor of MetS defined by three different international criteria in Caucasian women with PCOS (19). In the present study, we have confirmed that LAP is an independent predictor of MetS in each PCOS phenotype.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, we have shown a strong association between LAP and MetS in Caucasian PCOS population. Moreover, LAP had the highest diagnostic accuracy in comparison to other MetS determinants regardless of which MetS definition was used (NCEP-ATP III, IDF or JIS) (19). Since there is emerging evidence of variability of cardiometabolic risks in different PCOS phenotypes (8,20), the aim of this study was to evaluate the metabolic characteristics and prevalence of MetS, as well as to analyze the ability of LAP to predict MetS in different phenotypes of women with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we also observed a relationship between indices of liver steatosis and percent of body fat, HOMA-IR and HDL cholesterol in PCOS women. Similarly, in the previous study of the aforementioned authors, a correlation between LAP and the presence of insulin resistance, metabolic syndrome and impaired glucose tolerance in PCOS women has been shown (5, 26). All of these findings might have a therapeutic implication.…”
Section: Discussionsupporting
confidence: 74%
“…The three combined metabolic indices LAP, VAI, and TyG have been introduced as indicators of visceral adipose function and IR (15), which also could discriminate prediabetes and diabetes (17). In women with PCOS, LAP, a newly developed biomarker which mainly reflects the abdominal obesity, is associated with IR and MetS in women with PCOS (21,26,27). Polyzos et al (28) reported that LAP level is higher in PCOS patients with MetS than that in those without.…”
Section: Discussionmentioning
confidence: 99%